A precise, reproducible method for measuring ultrasound probe slice thickness using a Gammex 403 phantom. (August 2019) - Jackson, Steven J; Russell, Stephen
A precise, reproducible method for measuring ultrasound probe slice thickness has been developed for linear array ultrasound probes. The method used a custom built jig to draw the probe along the surface of a Gammex 403 phantom, with the image plane parallel to the filaments within the phantom. Still images at 0.5 mm intervals are saved for post-processing using in-house software. Slice thickness measurements with a precision of 0.1 mm are obtained. The method was shown to give reproducible estimates of probe slice thickness at several depths to within 0.4 mm during repeat tests. The method was able to provide information about the slice thickness of different sections of the probe face. It is expected that the method can quantify changes in probe performance due to lens wear or replacement over time that may elude both in-plane and in-air reverberation-based tests. A total of 18 linear probes were tested across eight centres, including six specialist vascular ultrasound centres.